1989
DOI: 10.1111/j.1476-5381.1989.tb11875.x
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to cromakalim in the rat uterus in vivo

Abstract: 1 Cromakalim (0.1 and mgkg 1) produced inhibition of uterine contractions and falls in mean blood pressure in ovariectomized, non-pregnant rats, the durations of which were dose-dependent. Frequency of contractions was inhibited selectively compared to amplitude. 2 The durations of the uterine effect of cromakalim (1 mg kg-1), when given at 12 h intervals, were less after the second, third and fourth doses compared to the first dose in non-pregnant rats. In ovariectomized rats treated from day 18 of pregnancy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1990
1990
1993
1993

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Cromakalim inhibits uterine contractions in vivo, is antagonized competitively by glibenclamide, a rela¬ tively selective blocker of ATP-sensitive potassium channels, and exhibits tolerance with repeated admin¬ istration (Downing et al 1989;Piper et al 1990;Downing & Hollingsworth, 19926). Potassium chan¬ nel opening may be part of the mechanism by which relaxin induces myometrial relaxation in vivo.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Cromakalim inhibits uterine contractions in vivo, is antagonized competitively by glibenclamide, a rela¬ tively selective blocker of ATP-sensitive potassium channels, and exhibits tolerance with repeated admin¬ istration (Downing et al 1989;Piper et al 1990;Downing & Hollingsworth, 19926). Potassium chan¬ nel opening may be part of the mechanism by which relaxin induces myometrial relaxation in vivo.…”
Section: Discussionmentioning
confidence: 97%
“…infusion of relaxin to non-pregnant ovariectomized rats (Cheah & Sherwood, 1981), suggesting that tolerance to relaxin may occur. ß-adrenoceptor agonists such as salbutamol (Abel & Hollingsworth, 1986;Downing & Hollingsworth, 1990, 19926) and potassium channel openers such as cromakalim (Downing, Miller & Hollingsworth, 1989 ; Downing Piper, Downing & Hollingsworth, 1991). It has been suggested that the development of tolerance to ß-adrenoceptor agonists may be due to three mechanisms: (i) phosphorylation of receptors, (ii) internalization and loss of membrane receptors and (iii) uncoupling of the membrane receptor from the adenylate cyclase complex with consequent loss of production of the second messenger, cyclic AMP (cAMP) (Harden, 1983 ;Lefkowitz, Hausdorff& Caron, 1990).…”
mentioning
confidence: 99%
“…Glibenclamide was also effective in reversing established uterine inhibition by cromakalim and appears to have stimulated uterine contractions above control values in these animals. Cromakalim has a prolonged duration of inhibition of uterine contractions (Downing et al, 1989). At 5 h after the control high dose of cromakalim (0.25mgkg-1), there may have been some residual effect of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Intrauterine pressure and its integral or blood pressure and heart rate were measured in conscious unrestrained rats and recorded on a Grass polygraph as described previously Downing et al, 1989 The same experimental design was adopted to measure the effects of cromakalim (0.1 mgkg-1) and RP 49356 (0.1 mgkg-') on blood pressure (BP) and heart rate (HR) before and after glibenclamide or vehicle infusion. Data are expressed as % change from pre-injection control values.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…The surgical technique was based on that of and Downing et al (1989). Rats were anaesthetized with tribromoethanol (240mgkg-1, i.p.…”
Section: In Vivo Studiesmentioning
confidence: 99%